Exploring the psychological attributes underpinning elite sports coaching. Issue 4 (August 2017) - Hodgson, Laura; Butt, Joanne; Maynard, Ian
The influential role of the coach in athlete performance and development has long been acknowledged, and coaches are now considered 'performers', just like their athletes. The purpose of the present study was to explore the psychological attributes elite coaches perceived to underpin their ability to coach most effectively and factors perceived to influence attribute development. Qualitative research methods were implemented where 12 elite coaches (eight male, four female) participated in semi-structured interviews. Inductive thematic analysis generated nine higher order themes related to psychological attributes: (a) attitude, (b) confidence, (c) resilience, (d) focus, (e) drive for personal development, (f) being athlete-centred, (g) emotional awareness, (h) emotional understanding, and (i) emotional management. In addition, three higher order themes were generated related to factors perceived to influence attribute development: (a) education, (b) experience, and (c) conscious self-improvement. Findings indicated that several attributes perceived to be essential to coaching effectiveness related to the emotional nature of coaching, where coaches' abilities to identify, understand, and manage emotions in both themselves and others had many positive effects.